Changes in Responsibilities and Tasks of Universities in Regional Innovation Ecosystems - Birkner, Zoltán; Máhr, Tivadar; Rodek Berkes, Nora (Naše gospodarstvo/Our economy, 2017)
Innovation process research is changing.In addition to the former territorial approach (examining countries or regions), the description of innovation cooperation in local areas is becoming more and more accepted. Instead of the innovation ability of the traditional large enterprises, research has begun to study the role of small and medium-sized enterprises, non-governmental organizations, local governments, and educational institutions (especially universities), which foreshadows the development of a new innovation system. In 2015, we conducted a study focusing on the civil and corporate relations of a major university. We tried to determine the new directions based on the economic and social cooperation as well as to search for the practical implementation of the theoretical helixes in these interactions. We came to the conclusion that universities not only are determinative according to the triple helix model but also have a prominent role in the creation of new innovation ecosystems, particularly in a well-defined geographical area.